Розвиток творчого самовираження дошкільників у мовленнєвій діяльності - Ткаченко, Альона Володимирівна (My University, 2020)
Кваліфікаційна робота виконана на теоретичному та практичному рівнях. На теоретичному рівні уточнено зміст та структуру провідних категорій, проаналізовано теоретико методичні засади творчого самовираження дошкільників. Розкрито значення мовленнєвої діяльності у процесі розвитку творчого самовираження старших дошкільників. Обґрунтовано педагогічні умови, форми та методи сприяння творчому самовираженню досліджуваних. На емпіричному рівні визначено критерії, показники та типи творчого самовираження дошкільників у мовленнєвій діяльності, досліджено вплив сім’ї та закладу дошкільної освіти на формування даної якості у дітей. Розроблено методику розвитку творчого самовираження дошкільників у мовленнєвій діяльності, перевірено її ефективність.
Qualification work is performed on theoretical and practical levels. At the theoretical level, the content and structure of the leading categories are specified, the theoretical and methodological principles of creative self-expression of preschoolers are analyzed. The importance of speech activity in the process of development of creative self-expression of senior preschoolers is revealed. The pedagogical conditions, forms and methods of promoting the creative self - expression of the subjects are substantiated. At the empirical level, the criteria, indicators and types of creative self-expression of preschoolers in speech activity are determined, the influence of family and preschool education institution on the formation of this quality in children is studied. The method of development of creative self-expression of preschoolers in speech activity is developed, its efficiency is checked. Key words: self-expression, creative self-expression, personal self-expression. speech self-expression, speech personality, creative abilities, word formation, word formation, speech creative activity.
Keywords: особистісне самовираження; мовленнєво-творча діяльність